EFFECT OF MASS MEDIA ON THE ADOPTION OF FISH CURING - NAIR, A. K. KESAVAN; KAUL, P N; BALASUBRAMANIAM, S (Fishery Technology, 2017)
A study of two factors with two-way classification shows that the main effect of newspaper subscription on the adoption of improved practices in fish curing is significant. The effect of radio ownership appears to be masked by newspaper subscription. The interaction between the two factors was not significant. The study confirms the importance of mass media in adoption.